The principle of effective demand and the labor market: theoretical approach of the Kaleckian Model of two goods for Ecuador - Varela, Marcelo (2017)
The principle of effective demand is a key to changing existing conditionalities labor market, where the production function of profit maximization change by a production function minimizing costs, based on an internal market approach that would change the element structural imbalances, allowing foreign market dependence is eliminated, therefore continuous fiscal deficits also be removed. This theoretical approach Kaleckian part of a performance for Ecuador of two goods models in which an expansion of the agricultural sector would result in an expansion of the industrial sector, consequently resulting in a greater labor demand that would stimulate wages based on a mechanism different of productivity that would change existing tensions or distributive conflict.